(untitled) (Fiep Bulletin - online, 2015)
The importance attached to physical education in school is justified by the role it has on the formation of new generations, influencing the acquisition of healthy habits and socially relevant learning, contributing to the full and harmonious personal and social development. Although excel as the only discipline capable of promoting the health of school to teach active lifestyles, suffers from a lack of legitimacy, not getting along to the school community presented in a clear way with defined objectives and content and the absence consensus among teachers against the various conceptions of teaching. It is in this scene and trying to contribute to the improvement of the status of physical education in school that this article discusses through the research results the potential of discipline in health promotion, the relationship with physical activity and academic performance of students. Finally, we see the conceptions of Physical Education reflecting on the most appropriate to promote active, healthy lifestyles and promoting physical activity in quantity, quality and intensity sufficient to meet the recommendations.